1975
DOI: 10.1046/j.1537-2995.1975.15676082242.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Control of Life‐Threatening Thrombocytosis with a Blood Processor

Abstract: A patient with polycythemia rubra Vera developed marked thrombocytosis and hemorrhage after splenectomy. Plateletpheresis with a blood processor proved to be a safe, efficient, and rapid method for the mechanical removal of large quantities of platelets prior to adequate control with chemotherapy. Medicine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In the meantime, therapeutic depletion of excess WBCs from CML patients was reported by Freireich and associates as a part of the NCI‐IBM cell separator development effort 15 . Although leukapheresis did not prove to be beneficial in this illness, the “proof of principle” provided by this experience set the stage for application of leukapheresis to patients with leukostasis in the context of acute leukemia and the use of therapeutic plateletpheresis 16 to address clinical manifestations of thrombocytosis.…”
Section: Clinical Application Of Tamentioning
confidence: 86%
“…In the meantime, therapeutic depletion of excess WBCs from CML patients was reported by Freireich and associates as a part of the NCI‐IBM cell separator development effort 15 . Although leukapheresis did not prove to be beneficial in this illness, the “proof of principle” provided by this experience set the stage for application of leukapheresis to patients with leukostasis in the context of acute leukemia and the use of therapeutic plateletpheresis 16 to address clinical manifestations of thrombocytosis.…”
Section: Clinical Application Of Tamentioning
confidence: 86%
“…Previous studies have shown that thombocyteapheresis can reduce the platelet count in a patient with thrombocytosis using intermittent ow centrifugation devices. 6,7 It is believed that patients with thrombotic or haemorrhagic manifestations associated with ET should be treated with thrombocyteapheresis in combination with cytoreductive therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Modern intermittent-flow and continuous-flow automated centrifugation systems are effective means of rapidly and effectively reducing platelet counts [63–65]. Currently used systems for platelet apheresis include COBE ® Spectra, Terumo ® Trima and Fenwal Amicus ® .…”
Section: Discussionmentioning
confidence: 99%